AB0204 THE CLINICAL FEATURES OF ANTI-TIF1GAMMA ANTIBODY POSITIVE DERMATOMYOSITIS. (June 2019) - Fujikawa, Yoshikazu; Akashi, Kengo; Katayama, Motoko; Yamashita, Mai; Nose, Yoko; Okano, Takaichi; Ueda, Yo; Sendo, Sho; Onishi, Akira; Saegusa, Jun; Morinobu, Akio
Abstract : Background: Anti-TIF1gamma antibody positive dermatomyositis(TIF1γ-DM) has greater risk of complication with cancer. Objectives: We aimed to analyze the clinical features of TIF1γ-DM and find the difference between cancer-associated TIF1γ-DM (CA-TIF1γ-DM) and non-cancer-associated TIF1γ-DM (nCA-TIF1γ-DM). Methods: We investigated the clinical data of idiopathic inflammatory myositis (IIM) patients received remission induction therapy in out hospital between January 2006 and December 2018. Results: We treated 148 patients with IIM in this period, 9 cases of them were TIF1γ-DM. Patients with CA-TIF1γ-DM and nCA-TIF1γ-DM were 4 and 5 cases, respectively. Average age at onset of 9 patients with TIF1γ-DM was 63 years old. CA-TIF1γ-DM was significantly older than nCA-TIF1γ-DM (average:78.0 vs 57.4). All of 9 TIF1γ-DM had distinctive skin rash and muscle weakness. Seven cases of them suffered from dysphagia. Interstitial lung disease was not seen in all patients with TIF1γ-DM. Serum creatine kinase (CK) levels of CA-TIF1γ-DM was significantly higher than those of nCA-TIF1γ-DM (average: 3405.5IU/L vs 719.8IU/L) (Fig 1 .). Among the TIF1γ-DM patients, we administered glucocorticoid (GCs) for 8 cases, immunosuppresants for 4 cases, and intravenous immunoglobulins (IVIG) for 7 cases. All 4 cases of CA-TIF1γ-DM were treated with GC and IVIG. All TIF1γ-DM patients, especially 4 CA-TIF1γ-DM patients, seemed to have good response to treatment in serum CK levels. Although serum CK levels of these 4 cases were normalized within a month (Fig1 .), their muscle weakness, skin rash and dysphagia which was associated with quality of life and the prognosis were poorly improved. Conclusion: In our investigation, the age of onset and serum CK levels were significantly different between CA-TIF1γ-DM and nCA-TIF1γ-DM. We report our investigation of the phenotype and treatment of anti TIF1gamma antibody positive dermatomyositis. TIF1γ-DM with high serum CK levels, we should perform appropriate tests to check for cancer throughout our treatment, and the improvement of serum CK levels is not equal to the success of our treatment. Disclosure of Interests: None declared